Optimization of the Use of Technology for Taxpayers in the Tax System in Indonesia - Tita, Heillen Martha Yosephine; Mustamu, Julista; Loupatty, Yopi Riszcy (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The development of tax reform shows that technology has a very important role. For this reason, the sustainability of tax collection in the State of Indonesia itself has at least an online system based on how taxpayers work to fulfill their obligations. However, the optimization of the application must be properly reviewed first to find out the effectiveness of the technology made.Purposes of the Research: This writing aims to study, analyze and discuss optimizing the use of technology in the taxation sector in Indonesia.Methods of the Research: This paper uses a normative research method, namely research that is focused on providing a systematic explanation that governs a certain category. The problem approach is the legal approach (statute opproach) and the conceptual approach (conceptual approach). The collection of legal materials through primary legal materials is then linked to secondary legal materials. Management and analysis of legal materials is described qualitatively with the aim of describing the findings in the field.Results of the Research: The results obtained from this paper are that, in principle, the technology used by the State of Indonesia is oriented to three pillars, namely: e-registration, e-filling and e-billing by means of technology that aims to strengthen taxpayer compliance. In addition, this technology has weaknesses, namely a good network and inefficient use of technology and the advantages of being able to access quickly and transparently.